The Effectiveness of the Singing Method in Enhancing Students’ Mastery of Arabic Vocabulary: A Systematic Literature Review - Jihadah; Muhamad Hasyim; Isna Seftiana Arni; Ahmad Nasrul Suhaedi; Kusuma Yanti; Indawati; Ardani Muhibbin; Alia Wulandari (Formad English Foundation NTB-Jakarta, 2026)
This study addresses the growing need for effective strategies to improve students’ mastery of Arabic vocabulary (mufradat), particularly amid persistent reliance on conventional memorization practices. The study aimed to examine the nature of the singing method and synthesize empirical evidence regarding its effectiveness in enhancing Arabic vocabulary mastery. A systematic literature review (SLR) was employed to analyze recent studies published primarily between 2021 and 2026. Relevant literature was identified through structured searching, screened using predetermined inclusion and exclusion criteria, assessed for methodological quality, and synthesized through descriptive comparison and thematic analysis. The findings revealed a predominantly positive pattern across the reviewed studies. Singing-based instruction improved vocabulary achievement, memorization, recall, pronunciation, motivation, and learner engagement. Quantitative studies reported substantial gains in post-test scores, N-Gain values, and statistically significant differences, while qualitative studies emphasized improved participation and more enjoyable learning experiences. The synthesis further indicated that effectiveness was strongest when singing was integrated with repetition, appropriate vocabulary selection, movement, visual support, and opportunities for recall and application. The study concludes that singing represents a promising, adaptable, and learner-centered strategy for Arabic vocabulary instruction. The findings contribute theoretically by strengthening understanding of multimodal vocabulary learning and practically by informing teachers’ instructional design. Future research should use larger samples, standardized measures, longer interventions, and stronger comparative designs.